Enhancement in reflection band width and omnidirectional reflection (ODR) bands in one-dimensional graded photonic crystal consisting of birefringent and dielectric materials - Kumar R.; Kushwaha A.S.; Srivastava S.K.; Pandey A.; Mishra H.; Srivastava S.K. (My University, 2025)
In the present paper, we theoretically investigate and study the reflection bands and ODR of one-dimensional graded photonic crystal structure having alternate layers of birefringent and dielectric materials for TE and TM polarization. The graded birefringent-dielectric photonic crystal (GBDPC) structure has a linear change in the thickness of the layers while the refractive index of the layers remains constant. In order to study the reflection bands, we calculate the reflectance spectra by using the transfer matrix method (TMM). From the analysis of the reflection curve it has been observed that the reflection band width and ODR band is enhanced by using GBDPC structure in comparison to non-GBDPC and dielectric dielectric photonic crystal (DDPC) structure, without changing the other parameters (number of layers and refractive index). © OSA 2014.